The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jafc.2c04213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial Activity, and Mechanisms of Novel Indole Derivatives Containing Pyridinium Moieties

Abstract: The development of effective antibacterial agents equipped with novel action modes and unique skeletons starting from natural compounds serves as an important strategy in the modern pesticide industry. Disclosed here are a series of novel indole derivatives containing pyridinium moieties and their antibacterial activity evaluation against two prevalent phytopathogenic bacteria, Xanthomonas oryzae pv. oryzicola (Xoc) and X. oryzae pv. oryzae (Xoo). A three-dimensional (3D)-QSAR model was adopted to discover hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In 2022, Li et al reported that indole derivatives 29 (Figure 5) containing pyridinium salts could regulate the conversion of glycolysis in rice to produce pyruvate, which was further decarboxylated to produce acetyl-CoA and subsequently entered the citric acid cycle where NAD + was reduced to NADH. The NADH produced by this process was fed into the oxidative phosphorylation way (Li et al, 2022a). The result of the two closely linked ways improves plant resistance to Xanthomonas oryzae pv.…”
Section: Biological Stress Resistancementioning
confidence: 99%
“…In 2022, Li et al reported that indole derivatives 29 (Figure 5) containing pyridinium salts could regulate the conversion of glycolysis in rice to produce pyruvate, which was further decarboxylated to produce acetyl-CoA and subsequently entered the citric acid cycle where NAD + was reduced to NADH. The NADH produced by this process was fed into the oxidative phosphorylation way (Li et al, 2022a). The result of the two closely linked ways improves plant resistance to Xanthomonas oryzae pv.…”
Section: Biological Stress Resistancementioning
confidence: 99%
“…Cyanoenone is an extended fragment of enone, in which cyano and carbonyl groups have the potential to interact with DNA or enzymes through hydrogen bonds, exists in various drugs, such as entacapone, teriflunomide ( Figure 1 ), and bardoxolone, exhibiting a broad range of pharmacological activities. Indole is a fused nitrogen-containing heterocycle, which can be used as a signal molecule to modulate multiple biological processes, including bacterial pathogenesis [ 23 , 24 , 25 ], and has been presented in many important pharmaceuticals, such as indolmycin, daptomycin, and indomethacin, displaying good pharmacokinetic properties [ 26 , 27 , 28 ]. Hence, introducing indolylcyanoenone composed of indole and cyanoenone into the coumarin scaffold might be an effective strategy to construct a new antibacterial framework against drug-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Indole and its derivatives have received copious attention for their physicochemical and pharmacological properties. Meanwhile, indole derivatives have broad-spectrum biological activities, such as antibacterial, anti-inflammatory, and antiviral. Therefore, commercial products with an indole backbone can be continually searched for in research and development in pesticides and pharmaceuticals. Recent studies have shown that the antiviral mechanism of most indole-containing compounds increases the plant body’s autoimmunity to fulfill disease rebellion. As a promising moiety in this category, 4,5-dihydro-1 H -pyrazoline exhibits diverse activities, which have led to the development of numerous commercially available drugs for application to insecticides, antivirals, herbicides, and fungicides. Thiourea is likewise an active structure, and its most well-known feature is its ability to serve as a hydrogen bond former, which helps strengthen the molecule’s binding to the probable target.…”
Section: Introductionmentioning
confidence: 99%